AKSESBILITAS DALAM PENGEMBANGAN POTENSI PARIWISATA DI KABUPATEN TOJO UNA-UNA PADA ERA REVOLUSI INDUSTRI 4.0 - Rizaldy H. A. Lakita (GoAcademica Research dan Publishing, 2021)
The purpose of this study is to determine the development of tourism potential, use of technology in developing tourism potential, and formulate strategies in developing tourism potential in the era of the industrial revolution 4.0. This study uses Cooper's theory related to tourism development as seen from 4 (four) indicators, namely attractions, amenities, accessbilities and ancillary services. The approach used in data analysis is SWOT analysis, which aims to analyze the use of technology in the development of tourism potential. This study uses a qualitative method with a descriptive approach by collecting data in the form of observations, interviews and documentation. The results show that the tourism potential development strategy has not been effective. In the application of 4 (four) tourism development indicators, namely attractions, amenities, accessbilities and ancillary services, there are still some shortcomings. The strategies used to increase the development of tourism potential in facing the era of the industrial revolution 4.0, namely: accelerating the preparation of Regional Regulations on the development of tourism based on technology; increasing budget resources for tourism development programs; improving the quality and quantity of human resources in technology-based tourism; and improving facilities and infrastructure in the development of technology-based tourism.